A MORPHOLOGICAL REVIEW OF FAÇADE PRECEDENTS EMPLOYING BIOMIMETIC DESIGN PRINCIPLES - Sultan Yazid (Universitas Mercu Buana, 2025)
The façade functions to separate the interior and exterior spaces of a building. This separation supports the building in providing protection from weather conditions, especially sunlight, for its occupants, and plays a role in reducing the building’s energy demand. At the same time, environmental issues pose distinct challenges for façade design, as environmental degradation increases the likelihood of rising global temperatures, which in turn leads to high energy use. Therefore, façade technology is required to be efficient and durable. One strategy to achieve this goal is the biomimetic approach. The research method uses a qualitative approach through the collection of secondary data in the form of façade precedents employing biomimetic principles. The sampling technique used is judgmental sampling, in which precedents are selected based on the architects’ narratives and the morphological characteristics that represent biomimetic principles. Two precedents from tropical and subtropical regions, Nicolas San Juan (Mexico) and The Alpha (Australia), were selected as case studies. The research stages include a literature review on façades and biomimicry, the development of a biomimetic assessment matrix, and the analysis of both precedents using the matrix to identify the application of biomimetic principles in façade design. This study is a foundational research that can be further developed by increasing the number of precedents and expanding the scope of biomimetic aspects, considering that this study is limited to morphological aspects and relies on secondary data. From this process, the research shows that both precedents successfully apply biomimetic principles consistently in their façade structures and patterns, thereby providing references for the development of biomimetic façade design in future studies.